IDENTIFIKASI PENYELESAIAN LINE STOP A&B CYLINDER HEAD PADA ROUGH RAW MATERIAL MENGGUNAKAN POKA YOKE - Indrawan Indrawan; Muhammad Rusydi; Rizki Dwi Afrianto (Sekolah Tinggi Teknologi Industri Padang, 2022)
In solving problems in this study background using the Poka Yoke method. PT. XYZ is the object of research this time and focuses on solving the Line Stop problem on Line A & B Cylinder Head on Rough Raw Materials. The purpose of the research for possible failure that occurs or has happened. After the failure is known, the next alternative problem solving is to prevent errors that will occur and/or activities/actions using the Poka Yoke method. The discovery in this study is known that the problem process when the spare part runs from the stopper at the shutter input rough raw material line A & B. So that it results in a spare part and exceeding work in procces (WIP) which can cause the IMSP-0011 engine to become a fault and line stop average 10 minutes per day. The results of this study using the Poka Yoke method through specific, measurable, achievable, reasonable and timephase (SMART) approaches which in essence are by adding Poka Yoke barrier to the stopper and changing ordinary nuts into nut lock. So the conclusion results of the implementation show the stopper functioning maximally, then the spare part according to the WIP.